CHALLENGES AND SOLUTIONS IN AFFORDABLE HOUSING CONSTRUCTION: A GLOBAL ANALYSIS - do Nascimento, Daniela Cristina (LUMEN ET VIRTUS, 2025)
Affordable housing construction has been one of the main global challenges in urban development, with countries such as Brazil, China, India, and advanced economies facing similar obstacles. In Brazil, the implementation of large housing projects, in partnership with Caixa Econômica Federal and municipal governments, has contributed significantly to reducing the housing deficit and ensuring decent housing for low-income families. These initiatives have been recognized for their quality and innovation, being essential for improving the living conditions of the population. However, challenges related to sustainability, ineffective management, and residential segregation remain issues to be resolved. Studies in other countries, such as China and India, show that although efforts to improve access to housing are being made, the lack of adequate infrastructure and regional disparities hinder the implementation of effective solutions. He, Yang, and Gong’s study (2023) highlights how the unbalanced real estate market in China exacerbates the crisis, and Singh, Yadav, and Deb’s research (2024) emphasizes the need for sustainable and inclusive solutions in India. In advanced economies like Sydney and Auckland, the market model has shown limitations in addressing the accessibility crisis. The analysis of these studies suggests that collaboration between the public and private sectors, the use of innovative technologies, and the development of effective public policies are essential to ensure that affordable housing becomes a sustainable and fair reality for all.